Attenuation of human hydatid cyst protoscolices viability by 1-Hydroxyphenazin (1-HP) pigment: In vitro and in vivo study - Zaman A. A. Ibrahim (مجلة كلية الطب, 2019)
Background: Hydatidosis is a widespread chronic zoonotic disease caused by helminthic larval stage of tapeworm Echinococcus granulosus. It has a serious medical and public health problem. Recently many substances are used to activate and modulate the immune system of the host in order to control the cyst growth and development. Materials and Methods: Protoscolices were isolated from human hydatid cysts and treated with four purified concentrations (25, 50, 75, 100μm/ml) of 1-HP plus hydatid cyst fluid as a positive control group for 4, 24, 48 and 72 hrs period of exposure. Then After 72 hours, the protoscolices which were treated with different concentration of 1-HP were inoculated intraperitonially of male white balb / c mice to see the infectivity of the protoscolices in vivo. Results: The results showed that the higher purified concentration 75,100 mole/ml of this pigment had a highly significant toxic effect on the viability of protoscolies, especially after 72 hrs.This toxicity of the pigment decreases the number of the protoscolices to develop and grow in vivo. Conclusion: It has been found that 1-hydroxyphenazine is a dose dependant toxic pigment causing attenuation of the protoscolices viability in vitro which decreases the number of protoscolices to develop and grow in vivo.